Plasma acceleration in the atmosphere by pulsed inductive thruster - Korytchenko, K. V.; Bolyukh, V. F.; Buriakovskyi, S. G.; Kashansky, Y. V.; Kocherga, O. I. (Національний технічний університет "Харківський політехнічний інститут", 2024)
One of the directions of development of plasma technologies consists in the formation of gas-metal plasma formations and throwing them to a certain distance. Known thrusters of plasma formation either have an electrode system that is prone to erosion, or a discharge system in a solid dielectric substance in which ablation occurs, or a complex gas-dynamic system with fuel supply. They do not provide acceleration of plasma formation in the atmosphere for a significant distance. Purpose. A theoretical and experimental study of electromechanical and thermophysical processes in a plasma thruster, which ensures the formation of a plasma formation due to thermal ionization by an induced current in a thin conductor layer during a high-voltage discharge on an inductor and the accelerating of a plasma formation in the atmosphere for a significant distance. Methodology. The proposed concept of a plasma thruster, in which the inductor inductively interacts with a combined armature, which includes an aluminum armature in the form of a thin (0.5-1 μm) foil, a copper armature made of a thicker foil (35-50 μm).On the basis of a mathematical model that takes into account the uneven distribution of currents in the inductor and conductive armatures, the features of the process of acceleration the combined armature in the atmosphere were established and experimental studies were carried out. Results. The electromechanical and thermal characteristics of the plasma thruster were calculated. It was established that the choice of the thickness of the dielectric layer of the armature, to which the aluminum and copper armatures are attached, is determined by the energy balance between the heating temperature of the aluminum armature and the electromechanical indicators of the thrower. Scientific novelty. It was experimentally established that the greatest density and homogeneity is observed in the middle of the plasma formation, which has the shape of a torus, moving away from the dielectric sheet on which the aluminum armature was located. As the voltage of the capacitive energy storage increases, the induced current density in the armature increases and the plasma formation becomes more uniform. Practical value. In comparison with the experimental results, the calculated current in the inductor coincides both in shape and in magnitude with an accuracy of 7 %. The biggest difference between the calculated and experimental currents of the inductor occurs when the aluminum armature is thermally destroyed. The transition of an aluminum armature into a plasma formation depends significantly on the voltage of the capacitive energy storage.

Один з напрямків розвитку плазмових технологій полягає у формування газо-металевих плазмових утворень та метанні їх на певну відстань. Відомі метальники плазмового утворення або мають електродну систему, яка схильна до ерозії, або розрядну систему в твердій діелектричній речовині, в якій відбувається абляція, або складну газодинамічну систему з подачею палива. Вони не забезпечують метання плазмового утворення в повітряному середовищі на значну відстань. Мета. Теоретичне та експериментальне дослідження електромеханічних та теплофізичних процесів в метальнику плазми, який забезпечує формування плазмового утворення за рахунок термічної іонізації індукованим струмом в тонкому провідникового шару при високовольтному розряді на індуктор та метання плазмового утворення у повітряному середовищі на значну відстань. Методика. Запропонована концепція метальника плазмового утворення, у якого індуктор індукційно взаємодіє з комбінованим якорем, що включає алюмінієвий якір у вигляді тонкої (0,5-1 мкм) фольги, мідний якір, який виконаний з більш товстої фольги (35-50 мкм). На базі математичної моделі, яка враховує нерівномірний розподіл струмів в індукторі електропровідних якорях, встановлені особливості процесу метання комбінованого якоря в повітряному середовищі та проведені експериментальні дослідження. Результати. Розраховані електромеханічні і теплові характеристики плазмового метальника. Встановлено, що, вибір товщини діелектричного шару якоря, до якого прикріплені алюмінієвий і мідний якоря, обумовлений енергетичним балансом між температурою нагріву алюмінієвого якоря і електромеханічними показниками метальника. Наукова новизна. Експериментально встановлено, що найбільша густина і однорідність спостерігається в середині плазмового утворення, яке має форму тора, що віддаляється від діелектричного листа, на якому розташовувався алюмінієвий якір. З підвищенням напруги ємнісного накопичувача енергії збільшується густина індукованого струму в якорі і плазмове утворення стає більш однорідним. Практична цінність. У порівнянні з експериментальними результатами розрахований струм в індукторі співпадає як за формою, так і за значенням з точністю до 7 %. Найбільша відмінність між розрахунковим і експериментальним струмами індуктора виникає при термічному руйнуванні алюмінієвого якоря. Перехід алюмінієвого якоря в плазмове утворення суттєво залежить від напруги ємнісного накопичувача енергії.
Keywords: plasma formation; pulsed inductive thruster; acceleration in the atmosphere; electromechanical and thermal processes; experimental research; плазмове утворення; імпульсний індуктивний метальник; прискорення в атмосфері; електромеханічні та теплові процеси; експериментальні дослідження